2021
DOI: 10.5194/acp-21-13855-2021
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric differences of mesosphere–lower thermosphere winds and tides investigated from three whole-atmosphere models and meteor radar observations

Abstract: Abstract. Long-term and continuous observations of mesospheric–lower thermospheric winds are rare, but they are important to investigate climatological changes at these altitudes on timescales of several years, covering a solar cycle and longer. Such long time series are a natural heritage of the mesosphere–lower thermosphere climate, and they are valuable to compare climate models or long-term runs of general circulation models (GCMs). Here we present a climatological comparison of wind observations from six … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 98 publications
(137 reference statements)
9
44
1
Order By: Relevance
“…The wind maxima are the strongest at TDF and KEP, and are weaker at ROT and DAV at higher latitudes, showing the amplitude change of the oscillation with latitude. These features are all consistent with properties of semidiurnal tides reported before (e.g., Murphy et al., 2006; Stober et al., 2021).…”
Section: Evaluation Of Navgem‐ha Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The wind maxima are the strongest at TDF and KEP, and are weaker at ROT and DAV at higher latitudes, showing the amplitude change of the oscillation with latitude. These features are all consistent with properties of semidiurnal tides reported before (e.g., Murphy et al., 2006; Stober et al., 2021).…”
Section: Evaluation Of Navgem‐ha Resultssupporting
confidence: 91%
“…The wind maxima are the strongest at TDF and KEP, and are weaker at ROT and DAV at higher latitudes, showing the amplitude change of the oscillation with latitude. These features are all consistent with properties of semidiurnal tides reported before (e.g., Murphy et al, 2006;Stober et al, 2021). Figure 10 shows that the semidiurnal tidal amplitudes from NAVGEM-HA are greater than those observed by the radars at TDF, KEP, and KSS but the tidal amplitudes are similar at ROT and DAV.…”
Section: Wind and Tidal Variations During The Sswsupporting
confidence: 87%
“…This is consistent with other meteor radar wind observations at high latitudes in both hemispheres (e.g. Fritts et al, 2010b;Sandford et al, 2010;Stober et al, 2021b). The vertical gradient of the zonal wind in summer is particularly strong, from around -20 ms -1 (westward) to up to +40 ms -1 (eastward) over only 10 to 15 km altitude.…”
Section: Comparison To a Traditional Height Gates Approachsupporting
confidence: 92%
“…Westward wintertime winds in the simulated polar MLT are a long-standing feature of WACCM (Harvey et al, 2019;Ramesh et al, 2020;Stober et al, 2021b), and they are also found in the thermospheric extension WACCM-X (Liu et al, 2010;Pedatella et al, 2014;Liu et al, 2018;Pancheva et al, 2020) and in other high-top models such as the MUAM (Lilienthal et al, 2018).…”
Section: Secondary Gws and Differences Between Radar Observations And Waccmmentioning
confidence: 84%
See 1 more Smart Citation